The Impact Analysis of Bauxite Downstreaming on the Indonesian Economy: Case Study in PT Bintan Alumina Indonesia - Jessica Andrea Shinta; Uka Wikarya (Borong Newinera Publisher, 2024)
This research analyzes the impact of investment and bauxite downstream activities by PT Bintan Alumina Indonesia (PT BAI) on the Indonesian economy using the input-output method applied to the Riau Islands Province, West Kalimantan Province and Indonesia. The imposition of stimulus on sectors related to the construction phase and operational phase of the alumina and aluminum industry in the Galang Batang SEZ is the concept that underlies how final demand in other sectors is affected. Economic improvement is characterized by increased output, GDRP, people's income, and the creation of job opportunities. During the construction phase of PT BAI (2016-2029), it generally had a positive impact on the increase in output, income, average GRDP, and average job creation in 52 industrial sectors in the Riau Islands Province. During the operational phase, calculated through three scenarios applied to the Riau Islands Province, West Kalimantan, and Indonesia, with the assumption of full downstreaming of PT BAI's products into the domestic market, shows the greatest impact. The impact includes the increase of Indonesia's output value until 2030 reaching IDR 547.07 trillion, an average annual GDP growth of 0.099 percent, a national income increases until 2030 reaching IDR 74.22 trillion, and an average job creation of 107,105 people per year in 52 industrial sectors in Indonesia. To achieve the optimal target of PT Bintan Alumina Indonesia's (BAI) presence in the domestic bauxite value chain, strengthening the downstream process and downstream industries of alumina and aluminum domestically is needed. Fiscal incentives, the establishment of pro-downstream regulations, and investor protection are crucial to implement.